The Habitat Perspective in Post-world War II Mediterranean Housing: A Space Syntax Analysis of Quinta da Malagueira (Portugal) and Carrières Centrales (Morocco) - Battal, Imran Gumus (Kim Williams Books, 2025)
This study examines the spatial organization of post-World War II Mediterranean housing through a comparative Space Syntax analysis of Quinta da Malagueira (QM) in Portugal and Carri & egrave;res Centrales (CC) in Morocco. It investigates the extent to which grid-based planning frameworks influence housing configurations, privacy hierarchies, and movement dynamics, mediating between modernist urban paradigms and vernacular spatial traditions. By employing Justified Plan Graph (JPG) and Visibility Graph Analysis (VGA), the research systematically evaluates the implications of modular grid planning on spatial accessibility, circulation networks, and social interaction. The findings reveal substantial disparities in spatial depth, integration, and visual permeability. QM exhibits a rigid spatial hierarchy, wherein courtyards function as mechanisms for regulating privacy and controlling movement. In contrast, CC supports a more fluid, interconnected spatial matrix, utilizing courtyards as semi-public transitional zones. Consequently, the grid-based planning approach is understood as a mediator between modernist architectural principles and localized cultural frameworks through the concept of habitat. This study contributes to the discourse on sustainable and contextually responsive urban planning, emphasizing the adaptive capacity of modular housing models. Moreover, it highlights Space Syntax as a robust analytical tool for quantifying privacy hierarchies and spatial legibility, offering critical insights into the development of human-centered, adaptable urban environments.
Keywords: Quinta da Malagueira; Carri & egrave;res centrales; & Aacute;lvaro Siza; Michel & Eacute;cochard; Housing; Habitat; Space syntax